Optimizing Pre-Calculation Skills of Kindergarten B Children Through Educational Games - Wahyu Ningrum, Nindiya; Laily, Nadhirotul (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Preschool education is widely recognized for its important role in building the early stages of a child's development before entering formal education. One potential method to support cognitive skills in children is through traditional games, such as congklak. The aim of this study is to describe the effect of using the congklak media in improving pre-math skills in kindergarten children at TK Al-Baqy. The research method used is experimental to test the effectiveness of the congklak game in enhancing children's pre-math skills. The intervention was conducted over 30 days with four meeting sessions. The program in this experiment focuses on improving pre-math skills through the congklak game as the main stimulus. In this context, the independent variable applied is the congklak game, while the dependent variable is the children's pre-math skills or early counting abilities. The results of the study show that the application of the congklak game as an intervention method can improve basic counting skills in children, changing the way they view mathematics with a fun and experiential approach. Positive reinforcement during the learning process also proved effective in increasing the children's self-confidence and learning motivation. The implications of this study are that game-based approaches can be an innovative solution in overcoming children's learning difficulties, increasing their interest in mathematics, and strengthening the social and emotional skills that are essential in child development.Pendidikan prasekolah secara luas diakui memiliki peran penting dalam membangun tahap awal perkembangan anak sebelum memasuki pendidikan formal. Salah satu metode yang potensial untuk mendukung keterampilan kognitif pada anak-anak adalah melalui permainan tradisional, seperti congklak. Tujuan penelitian ini untuk Penelitian ini  bertujuan untuk mendeskripsikan pengaruh penggunaan media congklak dalam meningkatkan kemampuan pra-berhitung pada anak TK B di TK Al-Baqy. Metode penelitian yang digunakan adalah eksperimen untuk menguji efektivitas permainan congklak dalam meningkatkan kemampuan pra-berhitung anak. Intervensi dilaksanakan selama 30 hari dengan durasi empat sesi pertemuan. Program dalam eksperimen ini berfokus pada peningkatan kemampuan pra-berhitung melalui permainan congklak sebagai stimulus utama. Dalam konteks ini, variabel independen yang diterapkan adalah permainan congklak, sementara variabel dependen adalah kemampuan pra-berhitung atau berhitung permulaan subjek. Hasil penelitian menunjukkan bahwa Penerapan permainan congklak sebagai metode intervensi dapat meningkatkan kemampuan berhitung dasar pada anak-anak, mengubah cara mereka memandang matematika dengan pendekatan yang menyenangkan dan berbasis pengalaman. Penguatan positif selama proses pembelajaran juga terbukti efektif dalam meningkatkan rasa percaya diri dan motivasi belajar anak. Implikasi dari penelitian ini adalah pendekatan berbasis permainan dapat menjadi solusi inovatif dalam mengatasi kesulitan belajar anak-anak, meningkatkan minat mereka terhadap matematika, serta memperkuat keterampilan sosial dan emosional yang esensial dalam perkembangan anak.